Cell Culture Optmization for the Baculovirus Expression Vector System (BEVS) - Yap, Wei Ney; Abdul-Rahman, Badarulhisam; Abdul-Aziz, Azila (2004)
An experiment was carried out to study the fundamental factors that affect the growth of Spodoptera frugiperda Sf-9 insect cells. Initial cell density, spent medium carry over and inoculum phase withdrawal significantly influenced the growth kinetics of Sf-9 cells. The percentage of cells infected with Autographa californica multiply-enveloped Nuclear Polyhedrosis Virus (AcMNPV) was obviously affected by spent medium carry over. On the other hand, initial cell density and Multiplicities of Infection (MOI) have minimal influence on infectivity percentage.